Communal Conflict and the Challenges of Development in Benue State: The Bonta-Okpute-Aino Experience - Tsuwa, John Tor; Adorowa, Janet Nguemo (Kashere Journal of Politics and International Relations, 2023)
The study investigated the impact of communal conflict on economic development in Benue State; with special focus on Bonta/Okpute-Aino communal conflicts. The purpose of the study was to find out the effects of communal conflicts on economic development. The study adopted the survey research design. The population of the study comprised 4,343 people living in Bonta and Okpute-Aino communities of Konshisha and Oju Local Government Areas of Benue State. A sample of 366 using a multi-stage sampling technique was selected for the study. Data were collected focus group discussions and key information interviews and the data analyzed using the political economy of resource scarcity theory. The findings revealed that the major causes of the communal conflict are land, boundary contestation precipitated by youthful exuberance, the lackadaisical attitude of the government towards boundary demarcation and the ego of the illustrious sons of the two communities. The actors in the conflict were revealed also. The government should also adopt a long term approach curbing communal disputes by developing early warning systems in the communities and adopt peace education suitable to tackle communal conflict in good time to prevent escalation. Basic amenities such as water, health facilities and electricity, should be provided for the communities to encourage small scale businesses. This will reduce idleness and poverty.